Do fathers care about their own immunisation status? The Child-Parent-Immunisation Survey and a review of the literature (Swiss Medical Weekly, 2020)
AIMS We recently conducted a large survey amongst parents of young children exploring attitudes concerning immunisation and the general immunisation status of the children and their parents in Switzerland. Since little is known about the immunisation status of fathers of young children, we present our findings here; data on mothers were previously published elsewhere. METHODS We performed standardised interviews with parents of children born on or after 1 January 2013, and hospitalised at the University of Basel Children’s Hospital, Switzerland, between January and June 2017. If participation was declined, partial consent was sought for four questions regarding age, education level, attitudes towards vaccinations in general and availability of vaccination records of the parents. To compare our study results with other studies focusing on the completeness of the immunisation status of fathers, we conducted a literature search using broad search terms for studies published between 1 April 2009 and 1 December 2019. RESULTS Thirty-nine (20%) fathers of 199 enrolled children participated. The great majority had a positive or mostly positive attitude towards vaccinations, but only 2 (15%) of 13 fathers who participated in immunisation counselling were up-to-date with all generally recommended immunisations. Fifty-two percent of participating fathers reported that the last assessment of their immunisation status by a physician was >5 years ago. After the birth of their child, 56% of fathers had received a recommendation for immunisation against pertussis and 65% of them followed the recommendation. We identified three studies matching our review’s inclusion criteria. None of them reported specific findings for fathers. CONCLUSIONS This is the first study to analyse the complete immunisation status of fathers of young children. It is often incomplete with potentially missed opportunities for updating vaccinations during recent physician consultations. The low participation rate of fathers is a limitation which prohibits generalisation of our findings. However, as healthcare personnel have been shown to have the strongest impact on vaccination uptake, we propose that this group be further sensitised and educated with the goal of improving immunisation rates in fathers of young children.